Iatrogenic Dysnatremias in Children with Acute Gastroenteritis in High-Income Countries: A Systematic Review - Grisaru, Silviu; Xie, Jianling; Samuel, Susan; Freedman, Stephen B. (Frontiers in Pediatrics, 2017)
Background: Acute infectious gastroenteritis (AGE) causing dehydration with or without dysnatremias is a common childhood health challenge. While it is accepted that oral rehydration therapy is preferred, clinical factors or parent and healthcare provider preferences may lead to intravenous rehydration (IVR). Isotonic solutions are increasingly recommended in most scenarios requiring IVR. Nevertheless, children with AGE, having ongoing losses of water and electrolytes, represent a unique population. Objectives: To evaluate the association between acquired dysnatremias and intravenous rehydration (IVR) in children with acute infectious gastroenteritis (AGE). Methods: A systematic search of MEDLINE database was conducted through September 14, 2016. Observational studies and clinical trials conducted in high-income countries were included. The GRADE (Grades of Recommendation, Assessment, Development and Evaluation) approach was used to evaluate the overall quality of evidence for each outcome. Results: 603 papers were identified of which 6 were included (3 randomized controlled trial and 3 observational studies). Pooling of patient data was not possible due to significantly different interventions or exposures. Single studies results demonstrated that within 24 hours, administration of isotonic saline was not associated with a significant decline in serum sodium while hypotonic solutions (0.2%-0.45% saline) were associated, in one study, with mean serum sodium declines from 1.3 mEq/L (139.2, SD 2.9 to 137.9, SD 2.5) in 133 young infants (aged 1-28 months), to 5.7 (SD 3.1) mEq/L in a subgroup of 18 older children (age mean 5.8, SD 2.7 years). Both isotonic and hypotonic saline were shown to be associated with improvement of baseline hyponatremia in different studies. Baseline hypernatremia was corrected within 4-24 hours in 81/83 (99.6%) children using hypotonic saline IVR. Conclusions: There is a paucity of publications assessing the risk for acquired dysnatremias associated with IVR in children with AGE. Current high quality evidence suggests that, short term use of isotonic solutions is safe and effective in most children with AGE; hypotonic solutions may also be appropriate in some subpopulations however the quality of available evidence is low to very low. Further research investigating outcomes associated with IVR use beyond 24 hours focusing on specific age groups is required.